Stamp Duty in Indonesia: Definition, Legal Sources, Subjects and Objects, and Application Rates - Alya An-Nais Syakilla; Bunga Citra Lestari; Dini Sapira Br Sembiring; Ruth Natalia Lumban Gaol; Windi Wulandari (CV. AFDIFAL MAJU BERKAH, 2025)
Stamp Duty is a tax on documents that are owed from the time the document is signed by interested parties, or the document is completed or submitted to another party if the document is only made by one party. The purpose of this research is to find out and understand stamp duty in Indonesia. This research also provides a comprehensive understanding of the meaning of tax, sources of tax law, tax subjects and objects, and tax application rates in the taxation system in Indonesia. using a normative approach based on Law Number 10 of 2020 concerning Stamp Duty, analysis was conducted on legal provisions and the application of stamp duty in both conventional and digital transactions. the results show that stamp duty has experienced tariff simplification and adjustments to digital documents, as well as with the development of information technology. A proper understanding of stamp duty is very important for taxpayers, business actors, and law enforcement officers in order to comply with administrative and efficiency in managing legal documents.